The Correction of the Addendum Radius of the Internal Gear in the Oil Hypocycloid Pump to Achieve Equal Wear Rates - Nguyen, Hong Thai; Truong, Cong Giang (Old Journal, 2019)
During the meshing process of a pair of internal hypocycloid gears, all of the mating teeth are in contact to their counterparts. In order to apply in designing rotary positive displacement pumps, one has used the variation of the tooth space to trap fluid and to force it around the outer periphery. The variation of the tooth space generates suction and discharge effects. During the meshing process, there is profile sliding between the teeth in each meshing pair, which results in unequal tooth wear. Therefore, practitioners have to select two parameters R₁ and rₒ for the rotor tooth profile during designing process. Up to date, the optimal combinations of these two parameters in order to achieve equal wearing rates have not yet been established. This paper presents a method for finding this relationship.